Dual effects of leptin in perioperative gas exchange of morbidly obese patients. - Michele Carron; Giovanna Ieppariello; Gabriele Martelli; Giulia Gabellini; Mirto Foletto; Egle Perissinotto; Carlo Ori (PLoS ONE)
Leptin has shown positive effects on respiratory function in experimental settings. The role of leptin on perioperative respiratory function in morbidly obese patients has not been established. We performed a retrospective analysis of morbidly obese patients undergoing laparoscopic sleeve gastrectomy. Fasting serum leptin and interleukin (IL)-6 were measured preoperatively, and arterial blood gases were obtained pre- and postoperatively. Outcome variables were arterial partial pressure of oxygen (PaO2), arterial partial pressure of carbon dioxide (PaCO2), and differences in PaO2 and PaCO2 between pre- and postoperative values (ΔPaO2, ΔPaCO2; postoperative minus preoperative). Patients with lower (<40 μg/L) and higher (≥40 μg/L) leptin levels were compared. Bravais-Pearson's correlation, multiple linear regression, and logistic regression analysis were performed. A total of 112 morbidly obese patients were included. Serum leptin was significantly higher in females than in males (42.86±12.89 vs. 30.67±13.39 μg/L, p<0.0001). Leptin was positively correlated with body mass index (r = 0.238; p = 0.011), IL-6 (r = 0.473; p<0.0001), and ΔPaO2 (r = 0.312; p = 0.0008). Leptin was negatively correlated with preoperative PaO2 (r = -0.199; p = 0.035). Preoperative PaO2 was lower, ΔPaCO2 was smaller, and ΔPaO2 was greater in the high leptin group than in the low leptin group. In multiple regression analysis, leptin was negatively associated with preoperative PaO2 (estimate coefficient = -0.147; p = 0.023). In logistic regression analysis, leptin was associated with improved ΔPaO2 (odds ratio [OR] = 1.104; p = 0.0138) and ΔPaCO2 (OR = 0.968; p = 0.0334). Leptin appears to have dual effects related to perioperative gas exchange in obese patients undergoing bariatric surgery. It is associated with worse preoperative oxygenation but improved respiratory function after surgery.